Efecto de la biofumigación para el control de nematodos en el suelo de un cultivo de banano (musa x paradisiaca) - Farez Gaona, Eduardo Joshue; Pineda Macas, Bryan Joel (Machala : Universidad Técnica de Machala, 2023)
Bananas play a vital role in the Ecuadorian economy, generating income, employment and stimulating investment in agricultural infrastructure. The presence of nematodes in the roots of banana plants has a detrimental impact, reducing yield, weakening the plants and affecting product quality, this entails significant control costs and threatens the long-term sustainability of the banana industry in Ecuador. For this reason, the objective of this work was to demonstrate the effectiveness of biofumigation through applications of compounds of plant origin in the soil of a banana crop, to reduce the amount of nematodes. The trial was carried out in the banana plantation of the “Santa Inés” experimental farm of the Faculty of Agricultural Sciences belonging to the Technical University of Machala, in the Province of El Oro; A completely randomized design was used to determine the behavior of the treatments. The compounds used for biofumigation were obtained from Brussels sprouts and nettle. The variables evaluated were: number of leaves (NH), diameter of the stem: (FS), height of the offspring until calving (AHP), weight of the cluster (PR), number of hands (NM), population of nematodes in three stages, percentage of live, dead and diseased roots; These variables were taken in three stages (initial, middle and final), after obtaining the information, a database was built in Excel for their respective analysis and interpretation. According to the results obtained, the one-factor ANOVA analysis determined that there was significance between the treatments because their values are less than (p= 0.05) with regard to the AHP and FS variables, significant differences were observed between at least a couple of groups, suggesting statistically notable variations. However, no significant differences in NH were found between the groups studied; the bilateral Dunnett's T test was used to make multiple comparisons between treatments T1 (OC10g), T2 (OC20g), T3 (OC30g) and the control group. T0 (OC0g) in relation to the same variables. In terms of AHP, treatments T3 (1.41m) and T2 (1.39m) showed significant differences with respect to the control group, indicating a positive effect on plant height. Regarding FS, only T3 (0.617m) showed a significant difference with the control group. However, in NH no significant differences were observed between the studied groups. The interpretation of graphs in production variables was carried out, which indicated that treatments T2 and T3 exhibited a greater bunch weight, with averages of 46.2 and 45.8 pounds respectively, in addition to an additional hand per bunch compared to T0. and T1, which could positively influence production. These treatments also demonstrated a significant increase in the percentage of healthy roots, T2 reaching 82.57% accompanied by T3 with 81.34%, as well as a reduction in diseased and dead roots, indicating an improvement in root health. Furthermore, T2 and T3 exhibited significant reductions in nematode population compared to T0, supporting the effectiveness of biofumigation in nematode control. These results underline the potential of biofumigation as a strategy to improve banana root quality and reduce the nematode population, which could have a positive impact on the productivity and overall health of banana plants, which is relevant. for Ecuador's banana industry.
El banano desempeña un papel vital en la economía ecuatoriana, generando ingresos, empleo y estimulando la inversión en infraestructura agrícola. La presencia de nematodos en las raíces de las plantas de banano tiene un impacto perjudicial, reduciendo el rendimiento, debilitando las plantas y afectando la calidad del producto, esto conlleva costos significativos de control y amenaza la sostenibilidad a largo plazo de la industria bananera en Ecuador, por este motivo se planteó como objetivo de este trabajo, demostrar la efectividad de la biofumigación mediante aplicaciones de compuestos de origen vegetal en el suelo de un cultivo de banano, para reducir la cantidad de nematodos. El ensayo se llevó a cabo en la plantación de banano de la granja experimental “Santa Inés” de la Facultad de Ciencias Agropecuarias perteneciente a la Universidad Técnica de Machala, en la Provincia de El Oro; se utilizó un diseño completamente al azar para determinar el comportamiento de los tratamientos. Los compuestos utilizados para la biofumigación fueron obtenidos de coles de Bruselas y ortiga. Las variables fueron evaluadas fueron: número de hojas (NH), diámetro del fuste: (FS), altura del hijo hasta la parición (AHP), peso del racimo (PR), número de manos (NM), población de nematodos en tres etapas, porcentaje de raíces vivas, muertas y enfermas; estas variables se tomaron en tres etapas (inicial, media y final), luego de obtener la información, se construyó una base de datos en Excel para su respectivo análisis e interpretación. De acuerdo con los resultados obtenidos, el análisis ANOVA de un factor, determinó que si hubo significancia entre los tratamientos debido a que sus valores son menores a (p= 0.05) en lo que respecta a las variables AHP y FS se observaron diferencias significativas entre al menos un par de grupos, lo que sugiere variaciones estadísticamente notables. Sin embargo, no se encontraron diferencias significativas en NH entre los grupos estudiados, en la prueba T de Dunnett bilateral se utilizó para realizar comparaciones múltiples entre los tratamientos T1 (OC10g), T2 (OC20g), T3 (OC30g) y el grupo de control T0 (OC0g) en relación con las mismas variables. En términos de AHP, los tratamientos T3 (1.41m) y T2 (1.39m) mostraron diferencias significativas con respecto al grupo de control, lo que indica un efecto positivo en la altura de las plantas. En cuanto a FS, solo el T3 (0.617m) mostró una diferencia significativa con el grupo de control. Sin embargo, en NH no se observaron diferencias significativas entre los grupos estudiados. Se realizo la interpretación de graficas en variables de producción lo que indico que los tratamientos T2 y T3 exhibieron un mayor peso de racimo, con promedios de 46,2 y 45,8 libras respectivamente, además de una mano adicional por racimo en comparación con T0 y T1, lo que podría influir positivamente en la producción. Estos tratamientos también demostraron un aumento significativo en el porcentaje de raíces sanas el T2 alcanzó el 82,57% acompañado del T3 con 81,34%, así como una reducción en las raíces enfermas y muertas, indicando una mejora en la salud radicular. Además, T2 y T3 exhibieron reducciones significativas en la población de nematodos en comparación con T0, respaldando la efectividad de la biofumigación en el control de nematodos. Estos resultados subrayan el potencial de la biofumigación como estrategia para mejorar la calidad de las raíces del banano y reducir la población de nematodos, lo que podría tener un impacto positivo en la productividad y la salud general de las plantas de banano, lo cual es relevante para la industria bananera de Ecuador.
Keywords: BIOFUMIGACION; NEMATODOS; BANANO; ENMIENDA ORGANICA